On One Class of Non-Dissipative Operators - Levchuk, V.N. (Журнал математической физики, анализа, геометрии, 2017)
The non-dissipative operator of integration is studied in the weight space. Its similarity to the operator of integration in the space without weight is proved. The functional model for this operator is obtained.